Preparation method of graphene conductive adhesive and graphene zinc-nickel battery using graphene conductive adhesive
Through the preparation and uniform dispersion technology of graphene conductive adhesive, the problem of difficult graphene dispersion in zinc-nickel batteries is solved, the charging and discharging performance and cycle life of the battery are improved, and the high energy density and safe zinc-nickel are achieved. Battery.
Patent Information
- Application Number
- CN202310871815.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
AI Technical Summary
The existing application of graphene in zinc-nickel batteries is difficult to disperse evenly due to the small amount of powder, resulting in poor battery performance consistency, failure to fully exert the conductive and thermal conductivity of graphene, affecting the charging and discharging performance and cycle life of the battery.
Using the preparation method of graphene conductive binder, the graphene aqueous dispersion is vacuum stirred with sodium carboxymethylcellulose and ultrapure water to form a uniformly dispersed graphene positive and negative electrode slurry, and the battery is prepared by slurry drawing process. The electrode sheet improves the conductivity and bonding performance of the adhesive, reduces the depowder of the electrode sheet, and enhances the cycle life and charge and discharge performance of the battery.
Achieve uniform dispersion of graphene in zinc-nickel batteries, improve the charging and discharging performance, cycle life and energy density of the battery, increase the power density to 2700 W/Kg, increase the energy density to 110 Wh/kg, and the safety of the electrolyte. Extremely high in nature.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catering, and in particular relates to a method for preparing a graphene conductive adhesive and a graphene zinc-nickel battery using the graphene conductive adhesive. Background Art
[0002] Graphene is a new type of carbon nanomaterial with remarkable physical and chemical properties. It is the thinnest, strongest, and most conductive and thermally conductive new type of nanomaterial discovered in the world. It is widely used in many fields, such as transparent conductive films, sensors, polymer composites, energy storage materials, biomedicine, thermal conductive coatings, anti-corrosion coatings, etc. Graphene is used in the battery field based on its conductive and thermal conductivity, which is lower than copper or silver, and is the best conductive material at room temperature. The best conductive and thermal conductivity at room temperature makes graphene an ideal application material for improving battery capacity, charge and discharge performance, high and low temperature performance, high rate discharge performance, and cycle life. The current method for applying graphene to zinc-nickel batteries is to add a very small amount of graphene powder to the positive and negative electrode powder materials, directly slurry and stir, or use physical methods to mix the powders first and then slurry and stir. Due to the extremely small amount of graphene powder, it is difficult to evenly disperse it in the positive and negative electrode powder materials through the above methods, resulting in a lack of outstanding battery performance improvement, or an improvement in battery performance but poor consistency, which fails to achieve the purpose of graphene application. In response to the application problem of graphene, this patent proposes a method for applying graphene to zinc-nickel batteries, namely, the preparation of a graphene conductive binder, and the use of this graphene conductive binder to mix and stir with positive and negative electrode powder materials. Graphene can be evenly dispersed in the positive and negative electrode powder materials. This positive and negative electrode slurry with evenly dispersed graphene is prepared into graphene positive and negative battery plates with good electrical performance consistency through a slurry pulling process. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing a graphene conductive adhesive and a graphene zinc-nickel battery using the graphene conductive adhesive. The various technical effects that can be produced by the preferred technical scheme among the various technical schemes provided by the present invention are described in detail below.
[0004] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: the preparation method and the materials involved include the preparation materials and preparation method process flow of graphene conductive binder, the preparation materials and preparation method process flow of graphene positive electrode sheet, and the preparation materials and preparation method process flow of graphene negative electrode sheet; the preparation method process flow of graphene conductive binder is divided into two parts, one is the process flow of graphene conductive binder used for preparing positive electrode sheet, and the other is the process flow of graphene conductive binder used for preparing negative electrode sheet; the graphene conductive binder is prepared and used to prepare the graphene conductive binder. The binder is mixed with the positive and negative electrode powder materials to form a slurry, and the graphene can be evenly dispersed in the positive and negative electrode powder materials. The positive and negative electrode slurry with evenly dispersed graphene is prepared into graphene positive and negative battery pole pieces with good electrical performance consistency through a slurry pulling process; thereby realizing the development of a new graphene zinc-nickel battery; the preparation materials of the graphene conductive binder include a graphene aqueous dispersion with a solid content of 0.4 to 0.5wt%, sodium carboxymethyl cellulose (CMC), and ultrapure water; the preparation materials of the graphene positive electrode piece include cobalt-coated spherical nickel hydroxide, nickel powder, calcium fluoride auxiliary material, and graphite for the positive electrode piece. The graphene negative electrode sheet preparation materials include zinc oxide, zinc powder, bismuth oxide, potassium fluoride auxiliary materials, graphene conductive binder for negative electrode sheet, and polytetrafluoroethylene emulsion (PTFE); the preparation method is to use the above materials and vacuum stirring equipment, alternately change the stirring speed of the stirrer under vacuum and constant temperature conditions, and synthesize the graphene dispersion with sodium carboxymethyl cellulose (CMC) according to specific process specifications. The synthesis process is divided into two stages: 1. vacuum stirring for 4-6 hours; 2. heat preservation and standing for 8-12 hours; the synthesized graphene The dilute conductive binder is mixed with the positive and negative electrode materials of the zinc-nickel battery respectively to make the positive and negative electrode sheets of the graphene zinc-nickel battery; due to the conductive modification of the binder, the proportion of the binder can be increased during the manufacture of the electrode sheet to enhance the bonding performance of the active material, the bonding performance of the active material and the electrode is improved, the powder shedding of the electrode sheet is reduced, especially the powder shedding of the negative electrode sheet, and the internal resistance is reduced; the graphene zinc-nickel battery composed of such graphene positive and negative electrode sheets has a higher rate discharge performance, improves the battery's charge and discharge performance, and increases the battery's cycle life; and the graphene battery has a high power density of 2700 W / Kg, and the energy density is increased from 75% to 110wh / kg; the graphene zinc-nickel battery electrolyte is a water-based electrolyte, which is extremely safe.
[0005] Preferably, the preparation materials of the graphene conductive adhesive include a graphene aqueous dispersion with a solid content of 0.4-0.5wt%, sodium carboxymethyl cellulose (CMC), and ultrapure water; the preparation method of the graphene conductive adhesive is divided into two parts, as follows: 1. Process flow of graphene conductive adhesive for preparing positive electrode sheet: Step 1: Weigh 4-6 wt% of graphene aqueous dispersion, weigh 1.5-4 wt% of sodium carboxymethyl cellulose (CMC), and weigh 90-94.5 wt% of ultrapure water; Step 2: First pour the ultrapure into the mixing barrel, then pour in the graphene aqueous dispersion, start the vacuum mixer, and stir at a speed of 200-300 rpm for 30 minutes; Step 3: Adjust the speed of the mixer to 100-200 rpm, and slowly add sodium carboxymethyl cellulose (CMC). After adding sodium carboxymethyl cellulose (CMC), continue stirring for 30 minutes; Step 4: Adjust the speed of the mixer to 300-500 rpm, stir in the vacuum state of the mixing barrel, and the stirring time is 240-360 minutes; During the above stirring process, the temperature of the binder is maintained between 20℃ and 40℃; Step 5: Place the stirred graphene conductive adhesive into a container and keep it warm for 8h-12h at a temperature between 20℃ and 30℃; 2. Process flow of graphene conductive adhesive used for preparing negative electrode sheets: Step 1: weigh 2-4 wt% of graphene aqueous dispersion, weigh 1.5-4 wt% of sodium carboxymethyl cellulose (CMC), and weigh 92-9.5 wt% of ultrapure water; Step 2: First pour the ultrapure into the mixing barrel, then pour in the graphene aqueous dispersion, start the vacuum mixer, and stir at a speed of 200-300 rpm for 30 minutes; Step 3: Adjust the speed of the mixer to 100-200 rpm, and slowly add sodium carboxymethyl cellulose (CMC). After adding sodium carboxymethyl cellulose (CMC), continue stirring for 30 minutes; Step 4: Adjust the mixer speed to 300-500 rpm, stir the mixture in a vacuum state, and stir for 240-360 min; During the above stirring process, the temperature of the binder is maintained between 20℃ and 40℃; Step 5: Place the stirred graphene conductive adhesive into a container and keep it warm for 8h-12h at a temperature between 20℃ and 30℃.
[0006] Preferably, the graphene positive electrode sheet preparation materials include cobalt-coated spherical nickel hydroxide, nickel powder, calcium fluoride auxiliary material, graphene conductive binder for positive electrode sheet, and polytetrafluoroethylene emulsion (PTFE); the graphene negative electrode sheet preparation materials include zinc oxide, zinc powder, bismuth oxide, potassium fluoride auxiliary material, graphene conductive binder for negative electrode sheet, and polytetrafluoroethylene emulsion (PTFE); 1. The process flow of the preparation method of the graphene positive electrode sheet is as follows: Step 1: Weigh 85-92 wt% of cobalt-coated spherical nickel hydroxide, 5-12 wt% of nickel powder and calcium fluoride auxiliary materials, 25-35 wt% of graphene conductive binder for positive electrode sheets, and 1-3 wt% of polytetrafluoroethylene emulsion (PTFE); Step 2: Put the above materials into the mixing barrel of the planetary mixer and stir them under vacuum to form graphene positive electrode slurry; Step 3: Prepare graphene zinc-nickel battery positive electrode sheets by passing the graphene positive electrode slurry through a positive electrode slurry drawing equipment and a nickel foam continuous automatic slurry drawing production line; 2. The process flow of the preparation method of the graphene negative electrode sheet is as follows: Step 1: weigh 75-85 wt% of zinc oxide, 10-20 wt% of zinc powder, bismuth oxide, and potassium fluoride auxiliary materials, 30-40 wt% of graphene conductive binder for negative electrode sheets, and 3-5 wt% of polytetrafluoroethylene emulsion (PTFE); Step 2: Put the above materials into a mixing barrel of a planetary mixer and stir them under vacuum to form a graphene negative electrode slurry; Step 3: Prepare graphene zinc-nickel battery negative electrode sheets by passing the graphene negative electrode slurry through a negative electrode slurry drawing equipment steel mesh continuous automatic slurry drawing production line; The positive and negative electrodes of the graphene nickel-zinc battery prepared above are assembled into graphene nickel-zinc batteries by winding or stacking them through a winding machine and a stacking machine. In addition to the positive and negative electrodes, the chargeable and dischargeable graphene nickel-zinc battery also has materials such as diaphragms, shells, tabs (columns), and electrolytes, which are known technologies in the battery field. The key technology for the quality of battery performance is the positive and negative electrode technology of the battery, including electrode materials, preparation processes, etc.
[0007] Preferably, the graphene carbon nanomaterial is a new type of nanomaterial with the strongest electrical conductivity. Graphene is added to the positive and negative electrode sheet materials of the nickel-zinc battery, and the adhesive is first modified, that is, a graphene conductive adhesive is first prepared, and then vacuum stirred with the positive and negative active substances (powders) to form positive and negative graphene slurries; in this way, the graphene can be evenly dispersed in the positive and negative electrode powder materials, and the positive and negative electrode slurries with evenly dispersed graphene are prepared into graphene positive and negative battery electrodes with good electrical performance consistency through a slurry pulling process; the adhesive is modified from being non-conductive to being conductive, and the proportion of the adhesive is appropriately adjusted to enhance the bonding performance of the active substance, the bonding performance of the active substance and the electrode, and the de-powdering of the electrode sheet, especially the de-powdering of the negative electrode sheet, is improved, and the battery cycle life is increased; the battery cycle The cycle life reaches 1000-1500 times; the graphene conductive adhesive is conductive, which reduces the internal resistance of the electrode. The zinc-nickel battery assembled with the electrode of the same thickness has better charge and discharge performance and higher rate discharge performance, and the 10C discharge efficiency is greater than 85%; higher specific energy, the mass energy density can reach 110Wh / Kg~130Wh / Kg, and the capacity is increased by 15-20%; the use of graphene conductive adhesive can increase the thickness of the electrode and reduce the use of electrodes and diaphragms while ensuring the battery's charge and discharge performance and cycle life. The graphene zinc-nickel battery with graphene conductive adhesive can further increase the volume specific energy, reduce the battery production cost, and improve the battery reliability.
[0008] Compared with the prior art, the present invention has the following beneficial effects: Compared with lithium batteries, the advantages of graphene zinc-nickel batteries are mainly reflected in: 1. High safety. Since graphene zinc-nickel batteries use aqueous solution, the battery is stable and will not explode even if thrown into a fire. However, lithium batteries can only use organic electrolytes. Lithium reacts chemically when it meets water, and aqueous solution does not work. Organic matter is prone to fire and expansion. 2. Environmental protection. Graphene nickel-zinc batteries have no memory effect. The main raw materials of nickel and zinc and their trace additives are non-heavy metal substances, and do not contain mercury or diaphragms. No pollutants are generated during the production and use process. The material recycling rate is more than 90%, and it is known as a truly green battery. 3. Long service life, the number of charge and discharge times can reach 500-600 times, which is 1.5~2 times that of lead-acid batteries. Through technological progress, the number of charge and discharge times can reach more than 1,000 times; Compared with other secondary batteries, the outstanding advantages of graphene zinc-nickel batteries are: high specific energy, high specific power, high open circuit voltage, wide operating temperature range (-20 ~ 60 ° C), high current charging, high discharge rate, abundant raw materials and low cost, and no environmental pollution. Due to the unique advantages of this battery, the research work on this system battery is very attractive and has broad application prospects as a future power source. Implementation
[0009] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0010] The present invention is further described below, but the protection scope of the present invention is not limited to the following description.
[0011] In the present embodiment, the preparation method and the materials involved include the preparation materials and the process flow of the preparation method of graphene conductive binder, the preparation materials and the process flow of the preparation method of graphene positive electrode sheet, and the preparation materials and the process flow of the preparation method of graphene negative electrode sheet; the process flow of the preparation method of graphene conductive binder is divided into two parts, one is the process flow of graphene conductive binder used for preparing positive electrode sheet, and the other is the process flow of graphene conductive binder used for preparing negative electrode sheet; the graphene conductive binder is prepared, and the graphene conductive binder is mixed with positive and negative electrode powder materials to mix and stir, and the graphene can be evenly dispersed in the positive and negative electrode powder materials. The positive and negative electrode slurry with evenly dispersed graphene is prepared into graphene positive and negative battery sheets with good electrical performance consistency through a slurry pulling process; thereby realizing the development of new graphene zinc-nickel batteries; the manufacturing equipment is an existing vacuum stirring equipment, which is manufactured according to the preparation materials and methods, and is alternately changed under vacuum and constant temperature conditions. The stirring speed is changed, and the graphene dispersion is synthesized with sodium carboxymethyl cellulose (CMC) according to specific process specifications. The synthesis process is divided into two stages: 1. Vacuum stirring for 4-6 hours; 2. Keeping warm and standing for 8-12 hours; The synthesized graphene conductive binder is mixed with the positive and negative electrode materials of the zinc-nickel battery respectively to make the positive and negative electrode sheets of the graphene zinc-nickel battery; Due to the conductive modification of the binder, the proportion of the binder can be increased during the manufacture of the electrode sheet to enhance the bonding performance of the active substance, and the active substance and The excellent bonding performance reduces the powder shedding of the electrode sheets, especially the powder shedding of the negative electrode sheets, and reduces the internal resistance at the same time; the graphene zinc-nickel battery composed of such graphene positive and negative electrode sheets has a higher rate discharge performance, improves the battery's charge and discharge performance, and increases the battery's cycle life; and the graphene battery has a high power density of 2700W / Kg, and the energy density is increased from 75% to 110wh / kg; the graphene zinc-nickel battery electrolyte is a water-based electrolyte with extremely high safety.
[0012] In this embodiment, the preparation materials of the graphene conductive adhesive include a graphene aqueous dispersion with a solid content of 0.4-0.5wt%, sodium carboxymethyl cellulose (CMC), and ultrapure water; the preparation method of the graphene conductive adhesive is divided into two parts, as follows: 1. Process flow of graphene conductive adhesive for preparing positive electrode sheets: Step 1: Weigh 4-6 wt% of graphene aqueous dispersion, 1.5-4 wt% of sodium carboxymethyl cellulose (CMC), and 90-94.5 wt% of ultrapure water; the requirements of the battery charge and discharge performance of the electrical products using the battery are not the same, and the wt% of each material used to prepare the graphene conductive binder used for the positive electrode should be different to meet the requirements of the electrical products for the battery charge and discharge performance; if a higher rate discharge performance is required, weigh 5.5 wt% of the total amount (wt) of the graphene conductive binder to be prepared in a mixing barrel, weigh 2wt% of sodium carboxymethyl cellulose (CMC), and weigh 92.5 wt% of ultrapure water; Step 2: First pour ultrapure water into the mixing barrel, then pour in the graphene aqueous dispersion, start the vacuum mixer, and stir at a speed of 200-300 rpm for 30 minutes; this step is to mix the graphene aqueous dispersion with the ultrapure water. According to the maximum stirring volume W of the mixing barrel, W1 / 4, W1 / 2, W3 / 4, and W, set the corresponding stirring speed to 200 rpm, 230 rpm, 260 rpm, and 300 rpm; Step 3: Adjust the mixer speed to 100-200 rpm, and slowly add sodium carboxymethyl cellulose (CMC). After adding sodium carboxymethyl cellulose (CMC), continue stirring for 30 min. In specific operation, according to W1 / 4, W1 / 2, W3 / 4, W of the maximum stirring volume W of the mixing barrel, set the corresponding stirring speed to 100 rpm, 130 rpm, 160 rpm, 200 rpm, and then use a small spoon to evenly and slowly add sodium carboxymethyl cellulose (CMC) from the material filling port of the mixer. After adding sodium carboxymethyl cellulose (CMC), maintain the set speed and continue stirring for 30 min. Step 4: Adjust the speed of the stirrer to 300-500 rpm, stir the stirring barrel under vacuum, and stir for 240-360 min. Increasing the stirring speed and time is to fully integrate sodium carboxymethyl cellulose (CMC) with ultrapure water and graphene aqueous dispersion. In specific operations, according to W1 / 4, W1 / 2, W3 / 4, and W of the maximum stirring volume W of the stirring barrel, set the corresponding stirring speed to 300 rpm, 130 rpm, 160 rpm, and 200 rpm, and the corresponding stirring time is 240 min, 280 min, 320 min, and 360 min. During the above stirring process, the temperature of the adhesive is kept between 20℃ and 40℃; the fusion performance of the adhesive is better in this temperature range, and in specific operation, the temperature of the adhesive only needs to be controlled in the range of 20℃ to 40℃; Step 5: Put the stirred graphene conductive adhesive into a container and keep it warm for 8h-12h, the temperature is between 20℃-30℃; through stirring, sodium carboxymethyl cellulose (CMC) has not been fully integrated with ultrapure water and graphene aqueous dispersion, and the purpose of keeping it warm is to fully integrate sodium carboxymethyl cellulose (CMC) with ultrapure water and graphene aqueous dispersion, so that the adhesive can achieve the best bonding performance. It can be no less than 8h, and it is useless to be more than 12h, and the normal room temperature of 20℃-30℃ is enough; 2. Process flow of graphene conductive adhesive used for preparing negative electrode sheets: Step 1: Weigh 2-4 wt% of graphene aqueous dispersion, 1.5-4 wt% of sodium carboxymethyl cellulose (CMC), and 92-9.5 wt% of ultrapure water; the requirements of the battery charge and discharge performance of the electrical products using the battery are not the same, and the wt% of each material used to prepare the graphene conductive binder used for the negative electrode should be different to meet the requirements of the electrical products for the battery charge and discharge performance; if a higher rate discharge performance is required, weigh 3.5 wt% of the total amount (wt) of the graphene conductive binder to be prepared in the mixing barrel once, weigh 3wt% of the graphene aqueous dispersion, weigh 3wt% of sodium carboxymethyl cellulose (CMC), and weigh 93.5 wt% of ultrapure water; Step 2: Pour the ultrapure water into the mixing barrel first, then pour the graphene aqueous dispersion into it, start the vacuum mixer, and stir at a speed of 200-300 rpm for 30 minutes; this step is to mix the graphene aqueous dispersion with the ultrapure water. According to the maximum stirring volume W of the mixing barrel, W1 / 4, W1 / 2, W3 / 4, and W, set the corresponding stirring speeds to 200 rpm, 230 rpm, 260 rpm, and 300 rpm; Step 3: Adjust the mixer speed to 100-200 rpm, and slowly add sodium carboxymethyl cellulose (CMC). After adding sodium carboxymethyl cellulose (CMC), continue stirring for 30 min. In specific operation, according to W1 / 4, W1 / 2, W3 / 4, W of the maximum stirring volume W of the mixing barrel, set the corresponding stirring speed to 100 rpm, 130 rpm, 160 rpm, 200 rpm, and then use a small spoon to evenly and slowly add sodium carboxymethyl cellulose (CMC) from the material filling port of the mixer. After adding sodium carboxymethyl cellulose (CMC), maintain the set speed and continue stirring for 30 min. Step 4: Adjust the speed of the stirrer to 300-500 rpm, stir the stirring barrel under vacuum, and stir for 240-360 min. Increasing the stirring speed and time is to fully integrate sodium carboxymethyl cellulose (CMC) with ultrapure water and graphene aqueous dispersion. In specific operations, according to W1 / 4, W1 / 2, W3 / 4, and W of the maximum stirring volume W of the stirring barrel, set the corresponding stirring speed to 300 rpm, 130 rpm, 160 rpm, and 200 rpm, and the corresponding stirring time is 240 min, 280 min, 320 min, and 360 min. During the above stirring process, the temperature of the adhesive is kept between 20℃ and 40℃; the fusion performance of the adhesive is better in this temperature range, and in specific operation, the temperature of the adhesive only needs to be controlled in the range of 20℃ to 40℃; Step 5: Put the stirred graphene conductive adhesive into a container and keep it warm for 8h-12h at a temperature between 20℃-30℃; through stirring, sodium carboxymethyl cellulose (CMC) has not yet fully and completely merged with ultrapure water and graphene aqueous dispersion. The purpose of keeping warm and standing is to achieve full and complete fusion of sodium carboxymethyl cellulose (CMC) with ultrapure water and graphene aqueous dispersion, and the adhesive achieves the best bonding performance; no less than 8h, more than 12h is also useless, normal room temperature 20℃-30℃ is sufficient.
[0013] In this embodiment, the graphene positive electrode sheet preparation materials include cobalt-coated spherical nickel hydroxide, nickel powder, calcium fluoride auxiliary material, graphene conductive binder for positive electrode sheet, and polytetrafluoroethylene emulsion (PTFE); the graphene negative electrode sheet preparation materials include zinc oxide, zinc powder, bismuth oxide, potassium fluoride auxiliary material, graphene conductive binder for negative electrode sheet, and polytetrafluoroethylene emulsion (PTFE); 1. The process flow of the preparation method of the graphene positive electrode sheet is as follows: Step 1: Weigh 85-92 wt% of cobalt-coated spherical nickel hydroxide, 5-12 wt% of nickel powder and calcium fluoride auxiliary materials, 25-35 wt% of graphene conductive binder for positive electrode sheet, and 1-3 wt% of polytetrafluoroethylene emulsion (PTFE); the requirements of the battery charging and discharging performance of the same electrical products using batteries are different, and the wt% of each material used to prepare the graphene positive electrode sheet is also different to meet the requirements of the electrical products for battery charging and discharging performance. If a higher rate discharge performance is required, weigh 86 wt% of the total amount (wt) of the graphene conductive positive electrode sheet slurry to be prepared in a mixing barrel, weigh 6 wt% of nickel powder and calcium fluoride auxiliary materials, weigh 35 wt% of graphene conductive binder for positive electrode sheet, and weigh 1.5 wt% of polytetrafluoroethylene emulsion (PTFE); Step 2: Put the above materials into the mixing barrel of the planetary mixer and stir them under vacuum to form graphene positive electrode slurry; in the specific operation, first pour the positive electrode graphene conductive binder into the mixing barrel, then close the lid of the mixing barrel, slowly add cobalt-coated spherical nickel hydroxide, nickel powder, and calcium fluoride auxiliary materials from the material filling port of the mixer, after adding, evacuate the mixing barrel, and stir for 3 hours under vacuum, finally add polytetrafluoroethylene emulsion (PTFE), and stir for another 1 hour to complete the preparation of the positive electrode sheet slurry; Step 3: Prepare graphene zinc-nickel battery positive electrode sheets by passing graphene positive electrode slurry through positive electrode slurry drawing equipment. The positive electrode slurry drawing equipment is a continuous automatic slurry drawing production line for nickel foam. The positive electrode slurry is sucked onto the nickel foam through a hopper, dried in an oven, and rolled into a positive electrode sheet with a thickness of 0.6 mm by a roller press. 2. The process flow of the preparation method of the graphene negative electrode sheet is as follows: Step 1: Weigh 75-85 wt% of zinc oxide, 10-20 wt% of zinc powder, bismuth oxide, and potassium fluoride as auxiliary materials, 30-40 wt% of graphene conductive binder for negative electrode sheets, and 3-5 wt% of polytetrafluoroethylene emulsion (PTFE); the requirements of the battery charging and discharging performance of the same electrical products using batteries are different, and the wt% of each material used to prepare the graphene negative electrode sheet is also different to meet the requirements of the electrical products for battery charging and discharging performance. If a higher rate discharge performance is required, weigh 80 wt% of the total amount (wt) of the graphene conductive negative electrode sheet slurry to be prepared in a mixing barrel, weigh 15 wt% of nickel powder and calcium fluoride auxiliary materials, weigh 38 wt% of graphene conductive binder for positive electrode sheets, and weigh 3.5 wt% of polytetrafluoroethylene emulsion (PTFE); Step 2: Put the above materials into the mixing barrel of the planetary mixer and stir them under vacuum to form graphene negative electrode slurry; in the specific operation, first pour the negative electrode graphene conductive binder into the mixing barrel, then close the lid of the mixing barrel, slowly add zinc oxide powder, zinc powder, bismuth oxide, and potassium fluoride auxiliary materials from the material filling port of the mixer, after adding, evacuate the mixing barrel, and stir for 3 hours under vacuum, finally add polytetrafluoroethylene emulsion (PTFE), and stir for another 1 hour to complete the preparation of negative electrode sheet slurry; Step 3: Prepare graphene zinc-nickel battery negative electrode sheets by using graphene negative electrode slurry drawing equipment; the negative electrode slurry drawing equipment is a copper mesh continuous automatic slurry drawing production line, the negative electrode slurry is sucked onto the copper mesh through a hopper, dried in an oven, and rolled into a positive electrode sheet with a thickness of 0.5 mm by a roller press; The positive and negative electrodes of the graphene zinc-nickel battery prepared above are assembled into a graphene nickel-zinc battery by winding or stacking. The graphene nickel-zinc battery that can be charged and discharged for recycling has, in addition to the positive and negative electrodes, a diaphragm, a shell, a pole ear (column), an electrolyte and other materials. The battery pole sheet winding or stacking process, as well as the diaphragm, the shell, the pole ear (column), the electrolyte and other materials are known general technologies in the battery field (including zinc-nickel batteries), and will not be described in detail in this patent. In this embodiment, the graphene carbon nanomaterial is a new type of nanomaterial with the strongest electrical conductivity. Graphene is added to the positive and negative electrode materials of the nickel-zinc battery. The adhesive is first modified, that is, a graphene conductive adhesive is first prepared, and then vacuum stirred with the positive and negative active substances (powders) to form positive and negative graphene slurries; in this way, the graphene can be evenly dispersed in the positive and negative electrode powder materials, and the positive and negative electrode slurries with evenly dispersed graphene are prepared into graphene positive and negative battery electrodes with good electrical performance consistency through a slurry pulling process; the adhesive is modified from being non-conductive to being conductive, and the proportion of the adhesive is appropriately adjusted to increase the bonding performance of the active substance, the bonding performance of the active substance and the electrode, and the de-powdering of the electrode, especially the de-powdering of the negative electrode, is improved, thereby increasing the battery cycle life; the electrical The cycle life of the battery reaches 1000-1500 times; the graphene conductive adhesive is conductive, which reduces the internal resistance of the pole piece. The zinc-nickel battery assembled with the pole piece of the same thickness has better charge and discharge performance and higher rate discharge performance than the zinc-nickel battery without the graphene conductive adhesive. The 10C discharge efficiency is greater than 85%; higher specific energy, the mass energy density can reach 110Wh / Kg~130Wh / Kg, and the capacity is increased by 15-20%; the use of graphene conductive adhesive can increase the thickness of the pole piece and reduce the use of pole pieces and diaphragms while ensuring the battery charge and discharge performance and cycle life. The graphene zinc-nickel battery with graphene conductive adhesive can further increase the volume specific energy, reduce the battery production cost, and improve the battery reliability; Comparison of discharge performance test between graphene zinc-nickel battery and conventional zinc-nickel battery: .
[0014] In this embodiment, the main structure of the graphene zinc-nickel battery is a zinc negative electrode and a nickel positive electrode; the zinc negative electrode is wrapped with a multi-layer diaphragm, which is divided into a liquid-absorbing diaphragm for storing electrolyte and a diaphragm for preventing zinc dendrites from penetrating; the electrode is led out with a pole ear; in addition to these basic components, the composition of the graphene zinc-nickel battery also includes electrolyte, air valve and battery casing, etc.; the graphene zinc-nickel battery can be made into batteries of various shapes, such as square and cylindrical batteries; the graphene zinc-nickel battery is based on the zinc-nickel battery, and the developed graphene battery has a high power density of 2700 W / Kg (lithium battery is 2000 W / Kg, while lead-acid batteries are 30W / Kg); energy density increased from 75% to 110wh / kg; graphene zinc-nickel battery electrolyte is a water-based electrolyte with extremely high safety, making it a good choice as a power battery; graphene zinc-nickel battery cost is lower than lithium battery, with the cost being one-third to two-thirds of that of power lithium battery; from the test data obtained, the battery voltage platform is improved, the energy density is improved, especially the high-rate discharge performance is improved, the 5C rate discharge efficiency is more than 90%, and the 10C rate discharge efficiency is more than 85%; graphene zinc-nickel battery will give full play to the characteristics of zinc-nickel battery, and is the first choice for high-safety power battery, which can be applied to electric bicycles, electric tools, electric vehicles and other products requiring high power and large capacity, and has huge market prospects.
[0015] In this implementation case, the graphene zinc-nickel battery is a graphene battery developed based on the zinc-nickel battery, and its performance characteristics are as follows: 1. The power density of graphene zinc-nickel battery is high, with a power density of 2700 W / Kg (lithium battery is 2000 W / Kg, lead-acid battery is 30W / Kg); energy density is 110wh / kg; 2. Graphene zinc-nickel batteries can be charged quickly, with a 1C charging efficiency of more than 95%; long cycle life: 100% discharge depth, more than 800 times; shallow discharge depth, more than 2,000 times; 3. The graphene zinc-nickel battery electrolyte is a water-based electrolyte with extremely high safety. It will not burn in case of fire, short circuit, collision, puncture, etc. It is a good choice as a power battery; 4. Graphene zinc-nickel batteries have a wide range of temperature adaptability, and low temperature rise during high current charging and discharging; 5. The cost of graphene zinc-nickel batteries is lower than that of lithium batteries. As a power battery, the cost price (RMB) of graphene zinc-nickel batteries is about 0.8-1.5 yuan / Wh, while that of lithium-based batteries is about 3-4.5 yuan / Wh; 6. The recycling rate of graphene zinc-nickel battery materials is as high as 90%, and the recycling cost is low, which is the highest among the commonly used batteries. The recycling rates of lead-acid batteries and lithium batteries are both lower than 10%. Therefore, when the production volume and holdings reach a certain scale, the recycling of materials can reduce the material cost, thereby reducing the production cost of batteries and greatly increasing the project benefits. Comparison of main indicators of commonly used batteries: Type Index Lead-acid batteries NiMH battery Lithium battery Zinc Air Graphene nickel-zinc battery Safety performance high Higher Very low Very high Very high Power density W / Kg 900 1300 2000 60-100 2700 Energy densityWh / Kg 30 65-70 110-130 180-220 110-130 Cost Yuan / Wh 0.7-1 4.5-5 6-15 0.5 0.8-1.5 Service life (times) 300 500-600 1500 〉300 800-1000 Recycling rate 0.1% 5% 3% 90% 90% pollute Very high Low Low none none Driving range per charge KM 80 100 500 〉500 300 .
[0016] In this implementation case, the specific application of the zinc-nickel battery is: 1. Due to its excellent power density and safety, zinc-nickel is a good power battery and can be used as a vehicle power battery. It can be applied to hybrid vehicles, pure electric vehicles, electric bicycles, electric motorcycles, sightseeing vehicles, electric scooters, etc. 2. As an electrical product battery, it can be used in: power tools, vacuum cleaners, strong light flashlights, mining lamps, emergency lights, police lights, photographic lights, camera power supplies, digital cameras, etc. 3. As solar and wind energy storage batteries, they can be used in: supporting power supplies for solar street lights, supporting power supplies for wind street lights, solar garden lights, solar charging lights, power supplies for solar (wind) supporting equipment, etc.; 4. Other applications: communication radio system power supply, weapon control system power supply, etc.
[0017] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected; the scope of the present invention to be protected is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a graphene conductive adhesive and a graphene zinc-nickel battery using the graphene conductive adhesive, characterized in that: The preparation method and the materials involved include the preparation materials and the process flow of the preparation method of graphene conductive binder, the preparation materials and the process flow of the preparation method of graphene positive electrode sheet, and the preparation materials and the process flow of the preparation method of graphene negative electrode sheet; the process flow of the preparation method of graphene conductive binder is divided into two parts, one is the process flow of graphene conductive binder used for preparing positive electrode sheet, and the other is the process flow of graphene conductive binder used for preparing negative electrode sheet; the graphene conductive binder is prepared, and the graphene conductive binder is used to mix and stir with positive and negative electrode powder materials, so that graphene can be evenly dispersed in the positive and negative electrode powder materials, and the positive electrode powder material with evenly dispersed graphene The negative electrode slurry is prepared into graphene positive and negative battery plates with good electrical performance consistency through a slurry pulling process; thereby realizing the development of a new graphene zinc-nickel battery; the preparation materials of the graphene conductive binder include a graphene aqueous dispersion with a solid content of 0.4-0.5wt%, sodium carboxymethyl cellulose (CMC), and ultrapure water; the preparation materials of the graphene positive electrode plate include cobalt-coated spherical nickel hydroxide, nickel powder, calcium fluoride auxiliary material, graphene conductive binder for positive electrode plate, and polytetrafluoroethylene emulsion (PTFE); the preparation materials of the graphene negative electrode plate include zinc oxide, zinc powder, bismuth oxide, potassium fluoride auxiliary material, graphene conductive binder for negative electrode plate, and polytetrafluoroethylene emulsion (PTFE); The preparation method is to use the above materials and vacuum stirring equipment, alternately change the stirring speed of the stirrer under vacuum and constant temperature conditions, and synthesize the graphene dispersion and sodium carboxymethyl cellulose (CMC) according to specific process specifications. The synthesis process is divided into two stages:
1. vacuum stirring for 4-6 hours; 2. heat preservation and standing for 8-12 hours; the synthesized graphene conductive adhesive is mixed with the positive and negative electrode materials of the zinc-nickel battery respectively to prepare the positive and negative electrode sheets of the graphene zinc-nickel battery; due to the conductive modification of the adhesive, the proportion of the adhesive can be increased during the manufacture of the electrode sheet to enhance the bonding performance of the active material, the bonding performance of the active material and the electrode, reduce the powdering of the electrode sheet, especially the powdering of the negative electrode sheet, and reduce the internal resistance; the graphene zinc-nickel battery composed of the graphene positive and negative electrode sheets has a higher rate discharge performance, improves the battery's charge and discharge performance, and improves the battery's cycle life; and the graphene battery has a high power density, with a power density of 2700. W / Kg, the energy density is increased from 75% to 110wh / kg; the graphene zinc-nickel battery electrolyte is a water-based electrolyte with extremely high safety.
2. According to claim 1, a method for preparing a graphene conductive adhesive and a graphene zinc-nickel battery using the graphene conductive adhesive, characterized in that The preparation materials of the graphene conductive adhesive include a graphene aqueous dispersion with a solid content of 0.4-0.5wt%, sodium carboxymethyl cellulose (CMC), and ultrapure water; the preparation method of the graphene conductive adhesive is divided into two parts, both of which use vacuum stirring equipment to prepare the graphene conductive adhesive, as follows:
1. Process flow of graphene conductive adhesive for preparing positive electrode sheet: Step 1: Weigh 4-6 wt% of graphene aqueous dispersion, weigh 1.5-4 wt% of sodium carboxymethyl cellulose (CMC), and weigh 90-94.5 wt% of ultrapure water; Step 2: First pour the ultrapure into the mixing barrel, then pour in the graphene aqueous dispersion, start the vacuum mixer, and stir at a speed of 200-300 rpm for 30 minutes; Step 3: Adjust the speed of the mixer to 100-200 rpm, and slowly add sodium carboxymethyl cellulose (CMC). After adding sodium carboxymethyl cellulose (CMC), continue stirring for 30 minutes; Step 4: Adjust the mixer speed to 300-500 rpm, stir the mixture in a vacuum state, and stir for 240-360 min; During the above stirring process, the temperature of the binder is maintained between 20℃ and 40℃; Step 5: Place the stirred graphene conductive adhesive into a container and keep it warm for 8h-12h at a temperature between 20℃ and 30℃; 2. Process flow of graphene conductive adhesive used for preparing negative electrode sheets: Step 1: weigh 2-4 wt% of graphene aqueous dispersion, weigh 1.5-4 wt% of sodium carboxymethyl cellulose (CMC), and weigh 92-9.5 wt% of ultrapure water; Step 2: First pour ultrapure water into the mixing barrel, then pour in the graphene aqueous dispersion, start the vacuum mixer, and stir at a speed of 200-300 rpm for 30 minutes; Step 3: Adjust the speed of the mixer to 100-200 rpm, and slowly add sodium carboxymethyl cellulose (CMC). After adding sodium carboxymethyl cellulose (CMC), continue stirring for 30 minutes; Step 4: Adjust the mixer speed to 300-500 rpm, stir the mixture in a vacuum state, and stir for 240-360 min; During the above stirring process, the temperature of the binder is maintained between 20℃ and 40℃; Step 5: Place the stirred graphene conductive adhesive into a container and keep it warm for 8h-12h at a temperature between 20℃ and 30℃.
3. A method for preparing a graphene conductive adhesive and a graphene zinc-nickel battery using the graphene conductive adhesive according to claims 1 and 2, characterized in that: The graphene positive electrode sheet preparation materials include cobalt-coated spherical nickel hydroxide, nickel powder, calcium fluoride auxiliary material, graphene conductive binder for positive electrode sheet, and polytetrafluoroethylene emulsion (PTFE); the graphene negative electrode sheet preparation materials include zinc oxide, zinc powder, bismuth oxide, potassium fluoride auxiliary material, graphene conductive binder for negative electrode sheet, and polytetrafluoroethylene emulsion (PTFE); 1. The process flow of the preparation method of the graphene positive electrode sheet is as follows: Step 1: Weigh 85-92 wt% of cobalt-coated spherical nickel hydroxide, 5-12 wt% of nickel powder and calcium fluoride auxiliary materials, 25-35 wt% of graphene conductive binder for positive electrode sheets, and 1-3 wt% of polytetrafluoroethylene emulsion (PTFE); Step 2: Put the above materials into the mixing barrel of the planetary mixer and stir them under vacuum to form graphene positive electrode slurry; Step 3: Prepare graphene zinc-nickel battery positive electrode sheet by passing graphene positive electrode slurry through positive electrode slurry drawing equipment; 2. The process flow of the preparation method of the graphene negative electrode sheet is as follows: Step 1: weigh 75-85 wt% of zinc oxide, weigh 10-20 wt% of zinc powder, bismuth oxide, and potassium fluoride auxiliary materials, weigh 30-40 wt% of graphene conductive binder for negative electrode sheets, and weigh 3-5 wt% of polytetrafluoroethylene emulsion (PTFE); Step 2: Put the above materials into a mixing barrel of a planetary mixer and stir them under vacuum to form a graphene negative electrode slurry; Step 3: Prepare graphene zinc-nickel battery negative electrode sheet by passing graphene negative electrode slurry through negative electrode slurry pulling equipment; The positive and negative electrodes of the graphene nickel-zinc battery prepared above are assembled into a graphene nickel-zinc battery by winding or stacking. In addition to the positive and negative electrodes, the chargeable and dischargeable graphene nickel-zinc battery also has materials such as diaphragms, shells, tabs (columns), and electrolytes, which are known technologies in the battery field. The key technology for the quality of battery performance is the positive and negative electrode technology of the battery, including electrode materials, preparation processes, etc.
4. A method for preparing a graphene conductive adhesive and a graphene zinc-nickel battery using the graphene conductive adhesive according to claims 1, 2 and 3, characterized in that: The graphene carbon nanomaterial is a new type of nanomaterial with the strongest conductive performance. Graphene is added to the positive and negative electrode sheet materials of the nickel-zinc battery, and the adhesive is first modified, that is, a graphene conductive adhesive is first prepared, and then vacuum-stirred with the positive and negative active materials (powders) to form positive and negative graphene slurries; in this way, the graphene can be evenly dispersed in the positive and negative electrode powder materials, and the positive and negative electrode slurries with evenly dispersed graphene are prepared into graphene positive and negative battery electrodes with good electrical performance consistency through a slurry pulling process; the adhesive is modified from being non-conductive to being conductive, and the proportion of the adhesive is appropriately adjusted to increase the bonding performance of the active material, the bonding performance of the active material and the electrode, and the powder shedding of the electrode sheet, especially the powder shedding of the negative electrode sheet, is improved, and the battery cycle life is increased; the battery cycle life is improved. The service life reaches 1000-1500 times; the graphene conductive adhesive is conductive, which reduces the internal resistance of the electrode. The zinc-nickel battery assembled with electrode pieces of the same thickness, the graphene zinc-nickel battery with graphene conductive adhesive has better charge and discharge performance than the zinc-nickel battery without graphene conductive adhesive, and higher rate discharge performance, 10C discharge efficiency is greater than 85%; higher specific energy, mass energy density can reach 110Wh / Kg~130Wh / Kg, and the capacity is increased by 15-20%; the use of graphene conductive adhesive can increase the thickness of the electrode piece and reduce the use of electrode and diaphragm while ensuring the battery charge and discharge performance and cycle life. The graphene zinc-nickel battery with graphene conductive adhesive can further increase the volume specific energy, reduce the battery production cost, and improve the battery reliability.